Antithrombotic Effects of Nur77 and Nor1 Are Mediated Through Upregulating Thrombomodulin Expression in Endothelial Cells. Issue 2 (February 2016) - Yang, Ping; Wei, Xin; Zhang, Jian; Yi, Bing; Zhang, Guan-Xin; Yin, Litian; Yang, Xiao-Feng; Sun, Jianxin
Abstract : Objective—: Thrombomodulin is highly expressed on the lumenal surface of vascular endothelial cells (ECs) and possesses potent anticoagulant, antifibrinolytic, and anti-inflammatory activities in the vessel wall. However, the regulation of thrombomodulin expression in ECs remains largely unknown. Approaches and Results—: In this study, we characterized nuclear receptor 4A family as a novel regulator of thrombomodulin expression in vascular ECs. We demonstrated that both nuclear receptors 4A, Nur77 and Nor1, robustly increase thrombomodulin mRNA and protein levels in human vascular ECs and in mouse liver tissues after adenovirus-mediated transduction of Nur77 and Nor1 cDNAs. Moreover, Nur77 deficiency and knockdown of Nur77 and Nor1 expression markedly attenuated the basal and vascular endothelial growth factor165 –stimulated thrombomodulin expression. Mechanistically, we found that Nur77 and Nor1 increase thrombomodulin expression by acting through 2 different mechanisms. We showed that Nur77 barely affects thrombomodulin promoter activity, but significantly increases thrombomodulin mRNA stability, whereas Nor1 enhances thrombomodulin expression mainly through induction of Kruppel-like factors 2 and 4 in vascular ECs. Furthermore, we demonstrated that both Nur77 and Nor1 significantly increase protein C activity and inhibit tumor necrosis factor α–induced prothrombotic effects in human ECs. Deficiency of Nur77 increases susceptibility to arterial thrombosis, whereas enhanced expression of Nur77 and Nor1 protects mice from arterial thrombus formation. Conclusions—: Our results identified nuclear receptors 4A as novel regulators of thrombomodulin expression and function in vascular ECs and provided a proof-of-concept demonstration that targeted increasing expression of Nur77 and Nor1 in the vascular endothelium might represent a novel therapeutic approach for the treatment of thrombotic disorders. Abstract : Supplemental Digital Content is available in the text.